Teachers' Perceptions about Readability and Modification of Authentic Texts Chosen for Teaching Reading in the Vietnamese Context - Khang, Nguyen Duy (Journal of NELTA, 2011)
The article presents EFL teachers’ perceptions towards the readability of authentic texts and the ways of modifying authentic materials used in teaching reading. Essential tools to check the ease of understanding authentic texts are also suggested. The data was collected by means of a questionnaire and test. The findings show that awareness of readability and modification of authentic texts in teaching reading benefited both the teachers in facilitating their teaching process and the learners in their language acquisition. Key words: Reading; Readability; Text readability; Authenticity; Text modification; Language acquisition Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 89-97 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4613